A Sense of Powerlessness Fosters System Justification: Implications for the Legitimation of Authority, Hierarchy, and Government. Issue 1 (22nd April 2014) - van der Toorn, Jojanneke; Feinberg, Matthew; Jost, John T.; Kay, Aaron C.; Tyler, Tom R.; Willer, Robb; Wilmuth, Caroline
<x xml:space="preserve">Abstract</x> In an attempt to explain the stability of hierarchy, we focus on the perspective of the powerless and how a subjective sense of dependence leads them to imbue the system and its authorities with legitimacy. In Study 1, we found in a nationally representative sample of U.S. employees that financial dependence on one's job was positively associated with the perceived legitimacy of one's supervisor. In Study 2, we observed that a general sense of powerlessness was positively correlated with the perceived legitimacy of the economic system. In Studies 3 and 4, priming experimental participants with feelings of powerlessness increased their justification of the social system, even when they were presented with system‐challenging explanations for race, class, and gender disparities. In Study 5, we demonstrated that the experience of powerlessness increased legitimation of governmental authorities (relative to baseline conditions). The processes we identify are likely to perpetuate inequality insofar as the powerless justify rather than strive to change the hierarchical structures that disadvantage them.